2010
DOI: 10.1016/j.tibs.2010.04.004
|View full text |Cite
|
Sign up to set email alerts
|

cJun NH2-terminal kinase 1 (JNK1): roles in metabolic regulation of insulin resistance

Abstract: The cJun NH2-terminal kinase isoform JNK1 is implicated in the mechanism of obesity-induced insulin resistance. Feeding a high fat diet causes activation of the JNK1 signaling pathway, insulin resistance, and obesity in mice. Germ-line ablation of Jnk1 prevents both diet-induced obesity and insulin resistance. Genetic analysis indicates that the effects of JNK1 on insulin resistance can be separated from effects of JNK1 on obesity. Emerging research indicates that JNK1 plays multiple roles in the regulation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

6
138
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 142 publications
(151 citation statements)
references
References 71 publications
(123 reference statements)
6
138
1
Order By: Relevance
“…Studies using mice with Nestin-cre-mediated ablation of floxed Jnk1 in the brain demonstrate that JNK deficiency causes increased energy expenditure that prevents obesity (Belgardt et al 2010;Sabio et al 2010a). This analysis indicates that JNK-mediated suppression of energy expenditure is critically required for obesity development (Sabio and Davis 2010).…”
mentioning
confidence: 83%
See 2 more Smart Citations
“…Studies using mice with Nestin-cre-mediated ablation of floxed Jnk1 in the brain demonstrate that JNK deficiency causes increased energy expenditure that prevents obesity (Belgardt et al 2010;Sabio et al 2010a). This analysis indicates that JNK-mediated suppression of energy expenditure is critically required for obesity development (Sabio and Davis 2010).…”
mentioning
confidence: 83%
“…The cJun N-terminal kinase signaling (JNK) pathway (Davis 2000) is implicated in the development of obesity (Sabio and Davis 2010). Indeed, obesity is associated with increased JNK activity in human omental adipose tissue (Bashan et al 2007).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Jun N-terminal kinase JNK, also known as the stress-activated protein kinase, belongs to the mitogen-activated protein kinase (MAPK) superfamily and exists as ten different isoforms (80). Stress signals, such as hyperlipidemia, cytokines (IL6, TNFa), hypoxia, toxins, heat shock and drugs, can activate JNK, which binds and phosphorylates c-Jun in two different serine residues, Ser63 and Ser73 (81,82).…”
Section: The Intracellular Mediators Of Metabolic Inflammationmentioning
confidence: 99%
“…Phosphorylated c-Jun forms dimers with members of Fos (c-Fos), Jun (JunB, JunD) or ATF families, resulting in the assemblage of the transcription factor activator protein 1 (AP-1), which is an important regulator of inflammation, cytokine production, apoptosis, neurodegeneration, cellular differentiation, migration and proliferation (83). Studies have shown that the isoform JNK1 is implicated in the pathogenesis of insulin resistance, T2D and obesity (80,84). In experimental obesity, JNK1 is activated in the adipose tissue, leading to insulin resistance, because it catalyses the phosphorylation of IRS1 in serine residues (84).…”
Section: The Intracellular Mediators Of Metabolic Inflammationmentioning
confidence: 99%